The firm's evaluation of local research institutes and universities - an empirical analysis for Germany - Alexander Cordes; Ulrich Schasse (European Regional Science Association (ERSA), 2015)
Spatial proximity facilitates transfer of knowledge and technology between research institutes or universities (RIU) and firms. Against this background the location of research institutions and universities is often seen as an instrument of regional policy to promote knowledge flows and R&D activity of firms. One major practical challenge is, however, to bring together both actors. The matching process is often hindered by prejudices and lacking information about the capabilities and requirements on both sides. This study contributes to the spare empirical literature on this topic by analyzing the firms? attitudes towards proximate RIU. We make use of differentiated data on firm characteristics and their evaluation of certain location factors in the years 2006 and 2009 provided by the IAB establishment panel. Several research questions are investigated by applying ordered probit regression models. How are non-innovating firms or firms with low R&D activities rating their local RIU? Are there important differences between urban and rural regions or between large firms and SMEs? Do objective information such as size and specialization of the local universities affect the firm?s evaluation? How far is ?local? (distinguishing data at the NUTS3 and NUTS2 level)? Does a successful participation of local universities in the German ?Excellence Initiative? change the firms? attitude? The results indicate that firms which are expected to be open to collaboration with RIU (in terms of R&D, human capital, knowledge-intensive industries) are rating their local RIU higher than other firms. We suppose that firms are already self-selected to places where they find their suitable collaboration partners. Objective information about the universities such as specialization on STEM fields positively affects the evaluation of proximate RIU. Especially the universities? focus on mathematics and natural sciences (slightly surprisingly rather than engineering) makes them better off from the perspective of the individual firm. Furthermore, information about universities in the remaining NUTS 2 region exhibit larger effects than information on the NUTS 3 region. This indicates that firms have a larger distance in mind when thinking of their ?location? and ?proximity to RIU?. Another finding is that the announcement of the winning universities in the ?Excellence Initiative? which additionally funds scientifically excellent concepts does not affect the firms? view on the local RIU.
Keywords: I23; I28; O31; 330; proximity; university-industry linkages; universities of excellence; location fa